Voluntary Diving Exercise Improves Hippocampus-dependent Learning in Rats - Rahadian Yudo Hartantyo; Helen Eko Putro; Epa Yohana Toga Torop; Laksmindra Fitria; Mulyati Mulyati (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
Several physiological alterations that arise in response to hypoxemia conditions when diving are intended to protect oxygen-sensitive organs from the hypoxic condition. Hippocampus, known for its central function in memory formation, is sensitive to hypoxic conditions. This research aimed to study the effect of voluntary diving exercise (VDE) on the hippocampus-dependent learning performance of rats. Rats were divided into control and diving groups, with swim and voluntary diving exercises every day for 60 days, respectively. Observation of memory consolidation was carried out using Morris Water Maze (MWM) and Novel Object Recognition (NOR) tests. In the MWM test, the escape latencies in the diving group were shorter than those in the control group. Consistent results were obtained in the MWM probe trial which the time spent in the target quadrant was significantly longer in the diving group. Moreover, the diving group spent more time exploring the novel object in the NOR test. Based on the results, we can conclude that 60 days VDE significantly improves hippocampus-dependent learning capacity in trained rats.